STRATEGI BERDAKWAH DI RUMAH TAHANAN NEGARA (STUDI KASUS STRATEGI DAKWAH PROFESOR SALMADANIS BAGI WARGA BINAAN PEMASYARAKATAN DI RUMAH TAHANAN NEGARA KLAS IIB PADANG) - Asrul Harahap (UIN Imam Bonjol Padang, 2018)
Preaching is not only normative understanding of Islamic values, but also understanding human and environment condition as the target of preaching. In preaching activity, we often found many problems as Islamic values bias, poverty, illiteracy, violence, moral decadency, backwardness, etc. These problems can not be solved only with normative teaching. Therefore, a proper preaching strategy is a preaching with practice or development of preaching to give solution appropriated with problem faced by umat. However, this study was conducted with the purpose of exploring the Profesor Salmadanis’s preaching strategy towards the prisoners in detention class IIB Padang City. The method in this study was the presentation of the case study method with a descriptive narrative data. The study suggests that to obtain good results in preaching activities carried out against the prisoners, to be better to prepare themselves to face the future condition of the people when it came out, then it is totally dependent on the preaching strategy in which brought by the preacher itself.